Vascular endothelial growth factor in bipolar depression: A potential biomarker for diagnosis and treatment outcome prediction. (February 2020) - Castillo, Monica Feliz R.; Cohen, Arielle; Edberg, David; Hoppensteadt, Debra; Fareed, Jawed; Martin, Brendan; Halaris, Angelos
Highlights: VEGF has been implicated in the neurotrophic model of depression. Treatment resistant bipolar depression improves with adjunctive COX-2 inhibition. Plasma VEGF is increased in bipolar depression similar to major depression. Plasma VEGF may be a predictive biomarker for depression. Baseline VEGF did not predict treatment response. Abstract: Background: Vascular Endothelial Growth Factor (VEGF) has been implicated in the neurotrophic model of depression. We explored the potential role of VEGF in the pathophysiology of bipolar depression and potential utility as a diagnostic or outcome predictive biomarker. Methods: In a double-blind study, treatment-resistant bipolar depressed patients received Escitalopram and were randomized to receive add-on Celecoxib (26 participants) or Placebo (21 participants). There were 32 healthy controls. Plasma levels of VEGF were determined at three timepoints over eight weeks. Results: Bipolar patients had significantly higher VEGF levels at baseline compared to healthy controls. Logistic regression analysis revealed that the AUC is 0.67 and the VEGF cut point is 8.21. At all timepoints, patients receiving Celecoxib had comparable VEGF levels to those receiving Placebo. VEGF levels did not change significantly over time. Baseline VEGF was a poor predictor of treatment response with an AUC of 0.53. Conclusions: The increased VEGF in bipolar depression agrees with similar findings in major depressive disorder. A high VEGF level tended to accurately predict bipolar disorder, with apparent differential VEGF expression. Baseline VEGF did not predict treatment response, and levels did not change with treatment. Plasma VEGF may have diagnostic utility and guide personalized treatment.